Dry matter yield, P response and nutritive value of selected accessions of chamaecytisus palmensis (tagasaste) and Teline monspssulana (Montpellier broom) in the Ethiopian highlands - Berhe, Kahsay; Tothill, J.C. (1997)
Four accessions of the multi-purpose fodder tree, tagasaste (Chamaecytisus palmensis) and one of Montpellier broom (Teline monspessulana) were evaluated for dry matter yield, response to P fertiliser and nutritive value for livestock feeding, at 2 contrasting sites in the highlands of Ethiopia, one on a neutral pH alfisol soil, and the other on an acid nitosol. Montpellier broom was considerably lower yielding than tagasaste. There were substantial differences in dry matter yield between tagasaste accessions at both sites, but superior accessions were not consistent across sites. All accessions responded considerably to P fertiliser at the first harvest at Soddo, where the soil is known to be P deficient and to have high ability to fix Responses were inexplicably negligible at subsequent harvests. Some variation was evident in the parameters reflecting feed quality, but values were generally consistent with the expectations for leguminous feeds. Mortalities from Fusarium wilt were relatively high at the Soddo site, probably exacerbated by the seasonal waterlogging. Thus study underlines the need for research on how tagasaste fits into farming systems, taking into account establishment, management and utilisation of the plant, and to identify suitable well drained habitats for its successful growth.